1997
DOI: 10.1152/ajpcell.1997.273.6.c2057
|View full text |Cite
|
Sign up to set email alerts
|

Activated lymphocytes increase expression of 5-lipoxygenase and its activating protein in THP-1 cells

Abstract: The aim of this study was to investigate the regulation of the 5-lipoxygenase pathway of arachidonic acid metabolism by lymphocytes using the monocyte-like cell line, THP-1. When THP-1 cells were incubated over 4–7 days in 10% supernatant from lectin-activated human lymphocytes, their capacity to synthesize 5-lipoxygenase products was significantly increased. In contrast, the supernatant from nonactivated lymphocytes had no effect. The increase in capacity to synthesize 5-lipoxygenase products was mimicked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
2
7
0
1
Order By: Relevance
“…The effect of the lymphocyte conditioned medium could be mimicked by GM-CSF or interleukin 3 (IL-3) (81). Similar results were obtained with the monocyte-like cell line THP-1 (82), and the same group also found that dexamethasone could increase expression of 5LO and FLAP in these cells (83). IL-3 can stimulate expression of 5LO also in mouse mast cells (84).…”
Section: Upregulation Of 5-lipoxygenase During Differentiation: Effecsupporting
confidence: 77%
“…The effect of the lymphocyte conditioned medium could be mimicked by GM-CSF or interleukin 3 (IL-3) (81). Similar results were obtained with the monocyte-like cell line THP-1 (82), and the same group also found that dexamethasone could increase expression of 5LO and FLAP in these cells (83). IL-3 can stimulate expression of 5LO also in mouse mast cells (84).…”
Section: Upregulation Of 5-lipoxygenase During Differentiation: Effecsupporting
confidence: 77%
“…There is a marked increase in the quantities of 5-oxo-ETE only when neutrophils are pretreated with phorbol myristate acetate (PMA), which elevates NADP ϩ (Powell et al, 1994). Zhang and coworkers (1996) end products identified (Ring et al, 1996(Ring et al, , 1997Werz and Steinhilber, 1996;Bonizzi et al, 1997;Larsson et al, 1998;Werz et al, 2000). In the murine-elicited peritoneal macrophage, 5-oxo-ETE was also detected (Hevko et al, 2001;Heveko and Murphy, 2002).…”
Section: A Cofactors For Oxoeicosanoid Formationmentioning
confidence: 99%
“…GM-CSF stimulates the recruitment and activation of eosinophils via ␤ integrin-mediated adhesion to epithelial and endothelial cells (16) and prolongs eosinophil survival via inhibition of apoptosis (5,17,18). Moreover, GM-CSF stimulates activation of the 5-lipoxygenase pathway (19). In addition, murine models of asthma and dieselinduced hyper-responsiveness have demonstrated an association between epithelial cell-derived GM-CSF and airway hyper-responsiveness (20,21).…”
mentioning
confidence: 99%